Universitas Negeri Medan Analyzing the Application of the Theory of Career Selection and Development according to Tom Holland to Students: Nadia Chairani, Wafiq Fauziah, Raisya Adinda, Keyla Cahayati, Syahidatul Nisa Faculty of Education, Psychology Education Study Program, Guidance and Counseling, Medan State University Email: nadiachairani5@gmail.com , raisyaadinda77@gmail.com , wafiqfauziah14@gmail.com , syahidatulnisa97@gmail.com . - Nadia Chairani Lia (P3M STAI Kuningan, 2023)
Career guidance is one aspect of developmental guidance, so it is very necessary throughout a child's development. According to Holland, a very basic important element is that choosing and adapting a career is a reflection of a person's personality. One's career choice will represent an expansion of one's personality and an attempt to implement a broad range of personal behavioral styles within the context of one's work life. The subjects in this research were students in class IX-3 with a total of 30 students. The data collection technique used to analyze the data was by distributing questionnaires over a number of sheets of paper and analyzing them again using a Google Form review and the percentage results are then managed to find problems. This research uses primary data sources, the data analysis technique used is qualitative data analysis . So research results were found which showed that some students at the school did not have interest and talent in investigative and conventional environmental models. So that there is no suitability for applying Tom Holland's theory among students, which means that the problem is found in the field of learning, namely learning difficulties in understanding regular number calculations as well as well-organized language and the intellectual domain which influences the personality in determining the next career direction. because it is difficult to be an individual who is systematic and structured and has good and thorough planning. What role a counselor can play in providing career guidance services really depends on the focus of the career guidance/counseling they are dealing with.